Application of composition controlled nickel-alloyed iron sulfide pyrite nanocrystal thin films as the hole transport layer in cadmium telluride solar cells - Bastola, Ebin; Bhandari, Khagendra P.; Ellingson, Randy J. (Journal of materials chemistry. C, Materials for optical and electronic devices, 2017)
Here, we report hot-injection colloidal synthesis, characterization, and control of electronic conductivity of nickel-alloyed iron sulfide (Ni x Fe 1−x S 2 ) pyrite nanocrystals (NCs). The Ni-alloyed iron pyrite NCs were synthesized using iron (Fe) and nickel (Ni) bromides as Fe and Ni sources, and elemental sulfur (S) as a sulfur source. As Ni is incorporated into the iron pyrite (FeS 2 ) NCs, the X-ray diffraction (XRD) peaks shift towards lower diffraction angles indicating higher lattice constants of the alloyed NCs in accord with Vegard's law. Scherrer-analysis and scanning electron microscopy (SEM) imaging indicate that the average particle sizes of alloyed NCs are smaller compared to pure FeS 2 NCs. In UV-Vis-NIR spectra, the alloyed NCs have higher absorbance in the infrared (IR) region than pure FeS 2 NCs indicating Ni-alloyed NCs have higher densities of mid-band gap defect states. Based on thermal probe and Hall-effect measurements, the majority charge carriers in these alloyed NCs depend upon the material composition. Pure iron pyrite (FeS 2 ) and Ni 0.1 Fe 0.9 S 2 NCs show p-type conductivity while Ni 0.2 Fe 0.8 S 2 and higher Ni concentration alloys exhibit n-type conductivity. Application of these alloyed NC thin films as the hole transport layer for CdTe solar cells revealed that Ni 0.05 Fe 0.95 S 2 NCs perform best with the average increase in efficiency of ∼5%, with the best cell performing up to 8% better than the laboratory standard copper/gold (Cu/Au) cell.